Experimental Analysis of the Influence of a Compressed Natural Gas (CNG) - Air Mixer on Performance and Emissions in Partial Load CNG-Diesel Dual Fuel Engines - Betty Ariani; Frengki Mohamad Felayati; Moh. Arif Batutah (Universitas Muhammadiyah Magelang, 2024)
The energy crisis and the threat of global climate change have spurred various research efforts and alternative initiatives to find substitutes for fossil fuels, improve energy efficiency, and reduce emissions, especially greenhouse gases. The shipping industry is one of the contributors to global emissions that has received particular attention due to the increasing demand for maritime transportation services. The use of natural gas is considered a potential solution due to its relatively clean nature, abundant availability, and competitive pricing. The CNG-Diesel Dual Fuel Engine design is developed with the principle of using natural gas as an alternative fuel without replacing the existing diesel engine. Minimal modifications are made to the intake manifold to accommodate CNG entry. Despite its advantages, the development of dual fuel engines faces challenges, such as increased methane emissions due to the potential for incomplete combustion. This research conducts experimental studies on the use of a Venturi-like mixer in the intake manifold to enhance the homogeneity of the CNG-air mixture before entering the combustion chamber. Testing the mixer's influence is carried out under various CNG injection durations at low and high engine loads at constant speeds. The results indicate that the addition of the mixer does not immediately improve combustion quality or reduce emissions. Attention to conditioning the homogenous mixture at the required air-fuel ratio before entering the combustion chamber is crucial. The selection of the appropriate mixer design, diameter size, and placement of holes needs careful consideration